Uji Penghambatan α-Glukosidase dari Kombinasi Ekstrak Kunyit, Teh Hitam dan Jahe: The α-Glucosidase Inhibition Test from a Combination of Turmeric Extract, Black Tea, and Ginger - Akhmad Endang Zainal Hasan; Dimas Andrianto; Rara Annisaur Rosyidah (Universitas Djuanda, 2022)
Traditional medicines that can be used as α-glucosidase inhibitors are turmeric (Curcuma longa L.), black tea (Camellia sinensi L), and ginger (Zingiber officinale). It is necessary to research the use of a combination of tea, turmeric, and ginger in inhibiting the α -glucosidase enzyme. This study aims to determine the optimal combination of extracts of turmeric, black tea, and ginger in inhibiting the α-glucosidase enzyme. The research carried out was the measurement of IC50 values for the inhibition of α-glucosidase of each extract, and the inhibition of the enzyme α-glucosidase in combination. The results of the test of ethanol extract of turmeric, ginger and black tea water extract obtained the inhibition value of α-glucosidase with IC50 values of 9.48±0.05 g/mL, 66.64±0.44 g/mL and 9.52±0.25, respectively. F7 is a combination of turmeric, ginger and black tea which produces the highest α-glucosidase inhibition, which is 67.86±0.93%.